Dynamic Interleukin-6 Level Changes as a Prognostic Indicator in Patients With COVID-19 - Zeming Liu; Jinpeng Li; Danyang Chen; Rongfen Gao; Wen Zeng; Sichao Chen; Yihui Huang; Jianglong Huang; Wei Long; Man Li; Liang Guo; Xinghuan Wang; et al. (Frontiers Media S.A., 2020)
BackgroundInterleukin-6 (IL-6), a proinflammatory cytokine, has been reported to be associated with disease severity and mortality in patients with coronavirus disease 2019 (COVID-19). Yet, dynamic changes in IL-6 levels and their prognostic value as an indicator of lung injury in COVID-19 patients have not been fully elucidated.ObjectiveTo validate whether IL-6 levels are associated with disease severity and mortality and to investigate whether dynamic changes in IL-6 levels might be a predictive factor for lung injury in COVID-19 patients.MethodsThis retrospective, single-center study included 728 adult COVID-19 patients and used data extracted from electronic medical records for analyses.ResultsThe mortality rate was higher in the elevated IL-6 group than in the normal IL-6 group (0.16 vs 5%). Cox proportional hazards and logistic regression analyses for survival (adjusted hazard ratio, 10.39; 95% confidence interval [CI], 1.09-99.23; p = 0.042) and disease severity (adjusted odds ratio, 3.56; 95% CI, 2.06-6.19; p < 0.001) revealed similar trends. Curve-fitting analyses indicated that patient computed tomography (CT) scores peaked on days 22 and 24. An initial decline in IL-6 levels on day 16 was followed by resurgence to a peak, nearly in tandem with the CT scores.ConclusionIncreased IL-6 level may be an independent risk factor for disease severity and in-hospital mortality and dynamic IL-6 changes may serve as a potential predictor for lung injury in Chinese COVID-19 patients. These findings may guide future treatment of COVID-19 patients.